Electrophoresis Life Sciences Practical Applications - Boldura, Oana-Maria; Baltă, Cornel (IntechOpen, 2018)
Electrophoresis is a widely used method in the field of life sciences, having multiple practical applications in physical, chemical, biochemical, and molecular biology domains. This book contains 8 chapters depicting various applications of this technique in biochemistry, molecular biology, and physical chemistry. This book presents the link between the exposed method and its applications in a very explicit manner and offers a wide range of practical examples. The book provides not only a vision of actual methods but also their necessary further improvements and suggested developments. Therefore, a particular attention was given to the described techniques as true guidelines in the fields where electrophoresis is recommended, being useful for not only the scientists but also the laboratory clinicians.